Z badań nad początkami obrad Sejmu Wielkiego - Szczyglelski, Wojciech (Przegląd Nauk Historycznych, 2008)
One of the most signiflcant events associated with the beginning of the debates of the Great Seym (the debates started on 6th October 1788) was the transformation of the independence oriented deputies into a gentry parliamentary formation, which became an independent political subject able to influence the debates of the Seym and the situation of the Commonwealth. An important role in the process of shaping this formation was played by the signiflcant Seym sessions of 3rd and 21st /22nd November 1788, the accompanying commotion among deputies and an attempt at organizing separatist Seym debates under the presidency of Stanisław Małachowski (the Speaker of the Great Seym) at the beginning of November. Due to the obstructive attitude of the king, who wanted to defend the system of government based on the Permanent Council (dependent on Russia) the independence oriented deputies, aiming at overthrowing the Permanent Council and abolishing the Russian protectorate, had to, apart from the ordinary course of debates, resort to drastic political measures. Thus, they threatened to announce the Seym secesion, they started tumult riots and threatened to use force, violence and bloodshed. Consequently, the king withdrew from parliamentary obstruction making it possible to re-establish the normal course of Seym debates. However, as a result of the November Seym debates and the events mentioned above the independence oriented deputies outnumbered the King's party and liberated Poland from the dependence on Russia even though the Permanent Council was still not abolished at that time. The political activity, self-reliance and anti-senator tendencies of the independence oriented deputies increased remarkably. This is how the independence oriented deputies transformed into the gentry parliamentary formation and became an independent political subject accepted by the State elites as a real political partner in the Seym debates (at the beginning of the Seym by the Pulawy party and from 1790 also by the King); the gentry deputies strengthened their position in the Seym in relation to the Senate and the enlightened landed gentry gradually acquired the status of the real sovereign of the Commonwealth.